Additive-Coated Metallic Effect Pigments for Nanometallographic Prints
The method enhances metal appearance printing by using a donor surface with enhanced substrate compatibility and surface modifiers to achieve a durable, high-gloss metal layer on substrates, addressing inefficiencies and waste in existing methods.
Patent Information
- Application Number
- JP2024537068
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2022-12-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-21
Smart Images

Figure 2025502685000001 
Figure 2025502685000002 
Figure 2025502685000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for printing on a substrate, and more particularly to a method by which a layer having a metallic appearance can be applied to a substrate. [Background technology]
[0002] Various systems for printing layers with a metallic appearance on substrates, such as paper or plastic films, are known in the art. These systems belong to two broad categories: foil stamping or foil fusing. One of the main disadvantages of both these methods is the large amount of foil that is wasted in these processes, because the foil areas that are not transferred (transferred) to form the desired image on the substrate cannot be recovered for use in the same method. Metal foils are expensive, so these methods are relatively costly, because the foil can be used only once and only a small portion of the metal is effectively transferred to the substrate.
[0003] In WO2016 / 189515A9, a new method is disclosed, which allows printing of a layer with a metallic appearance on a substrate in a much more cost-effective manner and without waste of metal or metallized foil. In this method, individual metal particles are transferred onto the substrate through a donor roll, and the metal particles on the donor roll are replenished during the repeated process. Although this method does not have all the disadvantages of foil stamping or foil fusing, it has been found that the gloss of the metal layer obtained through this method is not very high and / or shows deterioration over time. Summary of the Invention [Problem to be solved by the invention]
[0004] Surprisingly, a method has been found which does not exhibit the various disadvantages of the above mentioned processes, in particular a method according to the invention is provided for printing a layer having a metallic appearance onto a substrate, this layer having a high gloss level, which does not exhibit degradation over time. [Means for solving the problem]
[0005] The method according to the invention relates to a method for printing on a surface of a substrate, which comprises: (a) providing a donor surface; (b) passing the donor surface through a coating station, from which it emerges coated with individual particles; and (c) repeating the steps of: i. treating a surface of a substrate such that the affinity of the particles for at least selected regions of the surface of the substrate is greater than the affinity of the particles for the donor surface; ii. contacting a surface of the substrate with a donor surface such that particles are transferred from the donor surface to only the treated selected areas of the surface of the substrate, thereby exposing areas of the donor surface through which the particles are transferred to corresponding areas of the substrate; and iii. thus producing a plurality of individual particles adhered to the treated surface of the substrate; iv. Returning the donor surface to the coating station to make the particle monolayer continuous, thereby allowing subsequent printing of images onto the surface of the substrate; wherein 50% by weight of the individual particles are metal pigments comprising a metal substrate and a surface treatment of the metal substrate, the surface modification being achieved by treating the metal substrate surface with at least one modifying agent, the at least one modifying agent being at least one modifying agent selected from the group consisting of phosphate esters, phosphonic esters, phosphonic acids, phosphinate esters, organofunctional silanes, organofunctional titanates, organofunctional zirconates, organofunctional aluminates, and mixtures thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The method may further comprise a cleaning step during which particles remaining on the donor surface after contact with the substrate are removed from the donor surface, thereby rendering the donor surface substantially free of particles before the next pass through the cleaning station. Such a cleaning step may be performed between each print cycle or periodically, for example between print jobs, between particle changes, etc. A print cycle corresponds to the period between subsequent passes of a reference point on the donor surface through a coating station, such passes resulting from the donor surface being movable relative to the coating station.
[0007] Particle-coated donor surfaces are used in a manner similar to the foils used in foil imaging, however, unlike foil imaging, damage caused by each print to the continuity of the particle layer on the donor surface can be repaired by recoating only those areas of the donor surface where a previously applied layer has been stripped and exposed by transfer to selected areas of the substrate.
[0008] The reason that the particle layer on the donor surface can be repaired after each print is that the particles are selected so that they adhere more strongly to the donor surface than to each other, resulting in the applied layer being substantially a monolayer of individual particles.
[0009] Preferably, in step b, the donor surface emerges from the coating station coated with a monolayer of particles. The term "monolayer" is used in this description to describe a layer of particles on the donor surface, where at least 60% of the particles are in direct contact with the donor surface, in some embodiments 70-100% of the particles are in direct contact with the donor surface, and in further embodiments 85-100% of the particles are in direct contact with the donor surface. Although some overlap may occur between particles in contact with such a surface, this layer may be only one particle deep over most of the area of the surface. A monolayer in this description is formed from particles that are in sufficient contact with the donor surface, and thus is typically a single particle thick. Direct contact means that the particles remain attached to the donor surface at the exit of the coating station, for example after a surplus extraction step, a polishing step, or any other similar step.
[0010] To obtain a mirror-like high gloss area on (selected parts of) the substrate, the selected surface must be sufficiently covered with particles, meaning that at least 70% of the selected surface is covered with particles, or at least 80%, or at least 90%, or at least 95% of the selected surface is covered with particles. The percentage of the area of a particular target surface that is covered with particles can be evaluated by many methods known to the skilled artisan, for example by determining the optical density, which may be combined with establishing a calibration curve of known coverage points by measuring reflected light, by measuring transmitted light if the substrate is sufficiently transparent, or by measuring reflected light taking advantage of the reflectivity of the particles.
[0011] A preferred method for determining the percentage area of an object surface covered by particles is as follows: A square sample with 1 cm sides is cut from the object surface (e.g., from a donor surface or from a printed substrate). The sample is analyzed by a microscope (which may be a laser confocal (Olympus™, LEXT OLS30ISU) or a light microscope (Olympus™, BX61 U-LH100-3)) at a magnification of up to ×100 (resulting in a field of view of at least about 128.9 μm×128.6 μm). At least three representative images are acquired in reflectance mode. The acquired images are analyzed using ImageJ, a public Java image processing program developed by the National Institute of Health (NIH). The images are displayed in 8-bit grayscale, and the program is instructed to propose a reflectance threshold that differentiates between reflective particles (relatively bright pixels) and gaps that may exist between adjacent or nearby particles (such voids appear as relatively dark pixels). A trained operator can modify the suggested threshold value if necessary, but typically validates it. An image analysis program is then run to measure the amount of pixels representing particles and the amount of pixels representing uncovered area of interparticle voids, from which the percentage area of coverage can be easily calculated. Measurements made on different image portions of the same sample are averaged. If the sample is printed on a transparent substrate (e.g., a translucent plastic foil), a similar analysis may be performed in transmission mode, with particles appearing as relatively dark pixels and voids appearing as relatively light. Results obtained by such methods, or by substantially similar analytical techniques known to those skilled in the art, are referred to as optical surface coverage, which may be expressed as a percentage or as a ratio.
[0012] If printing takes place over the entire surface of the substrate, a receiving layer, which is preferably an adhesive material, may be applied to the substrate by a roller before the substrate is pressed against the donor surface during step i.
[0013] Most preferably, a receiving and / or adhesive layer is applied in step i onto the substrate.
[0014] On the other hand, especially where printing occurs only in selected areas of the substrate, the adhesive or receptive layer can be applied by any conventional printing method, such as by a die or printing plate, or by jetting the receptive layer onto the surface of the substrate, In other embodiments, the receptive layer is applied to the substrate surface by an indirect printing method, such as by offset printing, screen printing, flexographic printing, or gravure printing.
[0015] As a further option, the entire surface of the substrate may be coated with an activatable receiving layer, which is selectively made "tacky" by suitable activation means. Whether selectively applied or selectively activated, the receiving layer in this case forms a pattern that constitutes at least a portion of the image to be printed on the substrate.
[0016] The term "tacky" is used here only to indicate that the substrate surface, or any selected areas thereof, has sufficient affinity for the particles so that the particles are separated from the donor surface and / or are retained on the substrate when the donor surface and substrate are pressed against each other at a printing station, and does not necessarily have to be sticky to the touch. To allow printing of patterns in selected areas of the substrate, the affinity of the receptor layer (optionally activated) for the particles must be higher than the affinity of the bare substrate for the particles. In the context of this application, the substrate is the term "bare" when it lacks a receptor layer, or in some cases a properly activated receptor layer. For many purposes, the bare substrate has substantially no affinity for the particles to allow selective affinity of the receptor layer, although some residual affinity is acceptable (e.g., when not visually detectable) or even desirable for certain printing effects.
[0017] The receiving layer may be activated, for example, by exposure to radiation (e.g., UV, IR, and near IR) before being pressed against the donor surface. Other means of receiving layer activation include temperature, pressure, humidity (e.g., rewettable adhesives), and even ultrasound, and such means of treating the receiving layer surface of the substrate can be combined to render a compatible receiving layer tacky.
[0018] The nature of the receiving layer applied to the surface of the substrate may vary, inter alia, depending on the substrate, with the mode of application and / or activation means selected, but such formulations are conventionally known and no further details are necessary to understand the present printing method and system. In brief, any thermoplastic, thermosetting, or hot melt polymer that is compatible with the intended substrate and exhibits sufficient adhesion, relative affinity, optionally upon activation, for the envisaged particles, may be used to implement the present disclosure. Preferably, the receiving layer is selected so as not to interfere with the desired printing effect (e.g., clear, transparent, and / or colorless).
[0019] The desired properties of a suitable adhesive material relate to the relatively short time required to activate the receiving layer, i.e., to selectively change the receiving layer from a non-tacky state to a tacky state, increasing the affinity of selected areas of the substrate, and thus sufficiently adhering to the particles to separate them from the donor surface. A fast activation time allows the receiving layer to be used in high speed printing. Adhesive materials suitable for the implementation of the present disclosure are preferably capable of activation during a time not longer than the time it takes for the substrate to move from the activation station to the printing station.
[0020] In some embodiments, activation of the receiving layer can occur substantially instantaneously upon printing. In other embodiments, an activation station or activation step can occur prior to printing, in which case the receiving layer can be activated in less than 10 seconds, or even less than 1 second, particularly less than about 0.1 seconds or even less than 0.01 seconds. This time is referred to in this description as the "activation time" of the receiving layer.
[0021] As already mentioned, a suitable receiving layer must have sufficient affinity with the particles to form a monolayer according to the present teachings. This affinity, which can alternatively be considered as an intimate contact between the two, must be sufficient to hold the particles on the surface of the receiving layer and may result from the relative physical and / or chemical properties of the layer and the particles. For example, the receiving layer may have a hardness that is high enough to provide a satisfactory print quality, but low enough to allow adhesion of the particles to the layer. Such an optimal range may be understood as allowing the receiving layer to be "locally deformable" at the scale of the particles, so that sufficient contact is formed. Such affinity or contact may additionally be increased by chemical bonding. For example, the material forming the receiving layer may be selected to have functional groups suitable for being held to the particles by reversible bonding (supportive non-covalent electrostatic interactions, hydrogen bonding, and van der Waals interactions) or by covalent bonding. Similarly, the receiving layer must be suitable for the intended print substrate, all of which are known to those skilled in the art.
[0022] The receiving layer may have a wide range of thicknesses, depending, for example, on the print substrate and / or the desired print effect. A relatively thick receiving layer may provide an "embossed" appearance, where the design is raised above the surface of the surrounding substrate. A relatively thin receiving layer may follow the contours of the surface of the print substrate, for example, for a rough substrate, allowing a matte appearance. For a gloss appearance, the thickness of the receiving layer is typically selected to mask the roughness of the substrate, thus providing a flat surface. For example, for very smooth substrates, for example for plastic films, the receiving layer may have a thickness of only a few tens of nanometers, for example for a polyester film (e.g. polyethylene terephthalate (PET) foil) with a surface roughness of 50 nm, a thickness of about 100 nm, while smoother PET films allow the use of even thinner receiving layers. Substrates with a relatively rough surface in the range of microns, or tens of microns, are advantageous when a gloss effect, and therefore some smoothing / masking of the substrate roughness, is desired, with a receiving layer having a thickness in the same size range or approximately this size range. Thus, depending on the substrate and / or desired effect, the receptive layer may have a thickness of at least 10 nm, or at least 50 nm, or at least 100 nm, or at least 500 nm, or at least 1,000 nm. For effects that are discernible by tactile and / or visual detection, the receptive layer may further have a thickness of at least 1.2 micrometers (μm), at least 1.5 μm, at least 2 μm, at least 3 μm, at least 5 μm, at least 10 μm, at least 20 μm, at least 30 μm, at least 50 μm, or at least 100 μm. Although some effects and / or substrates (e.g., cardboard, carton, textiles, leather, etc.) may require a receptive layer having a thickness in the millimeter range, the receptive layer thickness is typically no more than 800 micrometers (μm), and is up to 600 μm, up to 500 μm, up to 300 μm, up to 250 μm, up to 200 μm, or up to 150 μm.
[0023] After printing has been performed, i.e., after the particles have been transferred (transferred) from the donor surface to the tacky areas of the treated substrate surface (i.e., the receiving layer) by pressing, the substrate may be further treated, for example by application of heat and / or pressure, thereby fixing or polishing the printed image, and / or coating it with a varnish (e.g., a colorless or colored, transparent, semi-transparent, or opaque overcoat) to protect the printed surface, and / or overprinting it with a different color ink (e.g., forming a foreground image). Some post-transfer steps may be performed on the entire surface of the printed substrate (e.g., further pressing), while other steps may be applied only to selected parts of it. For example, a varnish may be selectively applied to parts of the image, for example to selected areas coated with particles, optionally providing additional color effects.
[0024] Any equipment suitable for performing such post-transfer steps may be referred to as post-transfer equipment (e.g., coating equipment, polishing equipment, pressing equipment, heating equipment, curing equipment, etc.). The post-transfer equipment may additionally include any finishing equipment conventionally used in printing systems (e.g., laminating equipment, cutting equipment, trimming equipment, punching equipment, embossing equipment, perforating equipment, draining equipment, bonding equipment, folding equipment, etc.). The post-transfer equipment may be any suitable conventional equipment, the integration of which in the present printing system will be apparent to one skilled in the art without the need for further detailed description.
[0025] In the method according to the present invention, the particles have at least 50% flaky metal substrate, preferably 75% of the particles have flaky metal substrate, more preferably at least 85%, and most preferably 95-100% of the particles have flaky metal substrate.
[0026] In a further embodiment, the flaky metal substrate preferably has an average (median) thickness (h) in the range of 10 to 500 nm, more preferably in the range of 15 to 100 nm, and most preferably in the range of 20 to 40 nm.50 In particular, very thin metallic pigments, especially aluminum pigments (h 50 = 15-40 nm), very good transfer (transfer) of the metal particles to the donor surface and to the substrate was obtained.
[0027] Generally, the thickness of metal or metallic particles can be determined by scanning electron microscopy (SEM). For this purpose, the particles are incorporated in a two-component clear coat, such as Autoclear Plus HS (Sikkens), at a concentration of about 10% by weight, applied with a sleeve brush to a film using a spiral applicator (wet film thickness 26 μm) and dried. After a drying time of 24 hours, cross sections of these applicator drawdowns are made. The cross sections are analyzed by SEM (Zeiss supra 35) using a SE (secondary electron) detector. For the value analysis of platelet particles, the particles need to be well oriented plane-parallel to the substrate, so that systematic errors in the tilt angle caused by misaligned flakes are minimized.
[0028] Here, a sufficient number of particles must be measured to provide a representative average value. Conventionally, about 50-100 particles are measured. 50 The h value is the median value of the grain thickness distribution measured using this method. 50 The -value can be used as a measure of the average thickness.
[0029] Thickness distribution of metal particles or metallic particles and h 50 A detailed procedure for determining the -value is also described in EP1613702B1.
[0030] In one embodiment of the method according to the present invention, the flaky metal substrate has an aspect ratio in the range of 1500:1 to 10:1, preferably 1000:1 to 50:1, more preferably 800:1 to 100:1, and the aspect ratio is smaller than the average pigment diameter (D 50 value) and average pigment thickness (h 50 It is defined as the ratio between the
[0031] Pigment size is typically indicated using D values, which indicate the quantiles of the volume average particle size distribution (particle size distribution) in frequency representation. Here, the numbers indicate the proportion of particles smaller than a particular size contained in the volume average particle size distribution. For example, D 50 The values indicate the size of 50% or less of the particles. These measurements are carried out, for example, by means of a laser granulometer, using a particle size analyzer (Sympatec, model: Helos / BR). The measurements are carried out according to the data provided by the manufacturer.
[0032] In one embodiment of the method according to the invention, the flaky metal substrate is selected from flaky substrates of aluminum, copper, zinc, gold bronze, chromium, titanium, zirconium, tin, iron, and steel, or pigments of alloys of these metals. In a preferred embodiment, the flaky metal substrate is aluminum, gold bronze, or copper, and in a most preferred embodiment, the flaky metal substrate is aluminum.
[0033] Metal substrates may also contain up to 30% by weight of the oxide, hydroxide, acid hydrate or mixtures thereof of the same metal on their surface. Thus, an aluminium substrate may contain up to 30% by weight of aluminium oxide.
[0034] Such metal oxide layers are typically native oxides formed on the metal substrate under ambient atmospheric conditions or conditions of metal flake production (e.g., milling processes), in such cases the modifier bonds to such native metal oxide.
[0035] The metal substrate may be produced by a milling process or by a PVD process (Physical Vapor Deposition). More preferred is a flake metal substrate produced by a PVD process, and most preferred is such a flake metal substrate is an aluminum pigment.
[0036] According to a preferred embodiment, the flaky metal substrate is surface-modified with a modifier, which is at least one of the following: (i) [RO] (n-o-p) P(O)(OR 1 ) o (OR 2 ) p Here, o=1 to 2, p=0 to 2, and n+o+p=3 or 2; or (ii)R (n-o-p) -P(O)(OR 1 ) o (OR 2 ) p And n+o+p=3 or (iii) RP(OR 1 )(OR 2 ) or (iv) R´-SiX3
[0037] where X is a hydrolyzable group, such as a halogen group or an alkoxy group (OR 3 ) and R 3 = methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl. 3 is methyl or ethyl. X may be a hydroxy group OH. R 1 and R 2 The moieties are independently H, a metal ion, or a linear or branched alkyl moiety of 1-4 C atoms, preferably H. R or R' are independently linear or branched alkyl, aryl, alkylaryl, or arylalkyl having 1-24 C atoms, preferably having 6-20 C atoms, more preferably having 8-18 C atoms. Preferred are alkyl moieties. These alkyl or aryl moieties may be further functionalized by functional groups. Such functional groups can introduce polar groups, which can specifically interact with the surface of the substrate and / or the donor surface.
[0038] With respect to formula (i), the sum of n, p and o is preferably three.
[0039] Preferably, the functional groups of the moieties R or R' are independently phosphonic acid, phosphate, amino, epoxy, acrylate, methacrylate, hydroxy, mercapto, thiol, cyano, isocyanate, carboxy, carbamate, ureido, or thioureido groups.
[0040] In some embodiments, the functional group is the same type of group that is attached to the metal pigment surface, preferably an additive such as an α,ω-diphosphonic acid or an α,ω-diphosphate ester.
[0041] n, o, and p are stoichiometric factors. They generally indicate the molecular species, and the phosphate ester of species (i) may be a mixture of monoesters or diesters. In a preferred embodiment, the alkyl moiety R is an alkyl group having 8 to 18 C atoms. Most preferred is R 1 is H, p=0, and the average o=0.8 to 1.8, more preferably the average o=1.0 to 1.7.
[0042] By "average of o" is meant the average over the distribution of different species (mono- and diesters) with respect to the stoichiometric factor o. A preferred embodiment of species (i) is isotridecyl phosphate or cetyl phosphate.
[0043] For species (ii), p+o=2 (monophosphonate) is preferred. Preferred embodiments of species (ii) are octylphosphonic acid (OPS) or laurylphosphonic acid.
[0044] Suitable organofunctional silanes according to (iv) are, for example, many representatives manufactured by Evonik and products sold under the trade name "Dynasylan". Such organofunctional silanes can form covalent or hydrogen bonds with the surface of the donor substrate or with a receiving layer on the substrate, or can simply form van der Waals forces. For example, 3-methacryloxypropyltrimethoxysilane (Dynasylan MEMO), vinyltri(meth)ethoxysilane (Dynasylan VTMO or VTEO), aminopropyltrimethoxysilane (Dynasylan AMMO), aminopropyltriethoxysilane (Dynasylan AMEO) or N2-aminoethyl-3-aminopropyltrimethoxysilane (Dynasylan DAMO) or 3-glycidoxypropyltrimethoxysilane (Dynasylan GLYMO) may be used.
[0045] Other examples of silanes are: isocyanatotriethoxysilane, 3-isocyanatopropoxyltriethoxysilane, vinyltriacetoxysilane, vinyltrichlorosilane, 3-methacryloxypropyltriethoxysilane, methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-methacryloxyethyltri-(meth)ethoxysilane, 2-acryloxyethyltri(meth)ethoxysilane, 3-methacryloxypropyltris(methoxy-ethoxy)silane, 3-methacryloxypropyltris(butoxyethoxy)silane, 3-methacryloxypropyltris(propoxy)silane, or 3-methacryloxypropyltris(butoxy)silane.
[0046] Instead of, or in addition to, such functional silanes, monopolar organofunctional silanes may be used, having the formula: (v)R´´zSiX (4-z) or (vi) R´R´´SiX2 In formula (v), z is an integer from 2 to 3, R" in formula (v) or (vi) is unsubstituted, unbranched or branched, alkyl chain with 1 to 24 C atoms or aryl group with 6 to 18 C atoms, or arylalkyl or alkylaryl group with 7 to 25 C atoms, or mixtures thereof, and X is a halogen group and / or preferably an alkoxy group. The R" moieties may be the same or independently different moieties. Preferred are alkylsilanes with alkyl chains in the range of 4 to 18 C atoms, or arylsilanes with phenyl groups. R" may also be cyclically bonded to Si, in which case z is typically 2. X is most preferably ethoxy or methoxy.
[0047] A mixture of organofunctional silanes having different z values may also be used.
[0048] Preferred examples of such monopolar organofunctional silanes are alkyl or aryl silanes, examples of which are butyltrimethoxysilane, butyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltrimethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and mixtures thereof.
[0049] Examples of silanes according to formula (v) or (vi) are vinylethyldichlorosilane, vinylmethyldichlorosilane, vinylmethyldiacetoxysilane, vinylmethyldiethoxysilane, phenylvinyldiethoxysilane, phenylallyldiethoxysilane, and phenylallyldichlorosilane.
[0050] In a preferred embodiment, a mixture of silanes of formula (iv) and formula (v) is used. Particularly preferred is a mixture of an aminosilane and an alkylsilane.
[0051] In a further embodiment (vii), the additive is an organofunctional silane that is a precondensed heteropolysiloxane. The precondensed heteropolysiloxane preferably comprises at least one aminosilane and at least one alkylsilane.
[0052] Preferred precondensed heteropolysiloxanes can be obtained from Evonik Industries AG, 45128 Essen, Germany, under the trade names Dynasylan Hydrosil 2627, Dynasylan Hydrosil 2776, Dynasylan Hydrosil 2909, Dynasylan 1146, and Dynasylan Hydrosil 2907. Particularly preferred water-based heteropolysiloxanes are Dynasylan Hydrosil 2627, Dynasylan Hydrosil 2776, Dynasylan Hydrosil 2907, and Dynasylan Hydrosil 2909.
[0053] According to a preferred embodiment of the present invention, the precondensed heteropolysiloxane is selected from the group consisting of Dynasylan Hydrosil 2627, Dynasylan Hydrosil 2776, Dynasylan Hydrosil 2909, Dynasylan 1146, Dynasylan Hydrosil 2907, and mixtures thereof.
[0054] Preferred are additives of types (i) to (v), and particularly preferred are additives of type (ii).
[0055] The additives provide the flake metal pigments with sufficient corrosion stability to survive in the aqueous medium of the coating station before the particles are transferred (transferred) to the donor surface. The flake metal pigments produced by milling techniques are coated with fatty acids, and these additives are not sufficient to allow corrosion stability for these effect pigments over a relatively long period of time. Thus, the gloss retention of these pigments in the printing process is not sufficient. Since the donor surface is usually very hydrophobic, the additives can also provide the surface of the flake metal pigments with sufficient hydrophobicity. On the other hand, the additives may be selected to additionally have functional groups that are very compatible with the chemistry of the receiving layer and thus allow good transfer to the adhesion layer or to the part of the substrate coated with the receiving layer.
[0056] The particles used in the method according to the invention are prepared by dispersing the initial metallic particles in an organic solvent, optionally heating to the boiling point of the particle solvent used at a temperature of 20°C, more preferably at a temperature of 40-80°C, and mixing with a small but suitable amount of a solution of the additive in the organic solvent.
[0057] In particular, for metal pigments obtained by milling, the filter cake obtained may be dried in vacuum at about 60-130° C. and different solvents may be added. For some surface modifiers, it is not necessary to heat the mixture, since for these substances simple mixing may be sufficient.
[0058] For the mixing step, mixer-agglomerators customary for metal effect pigments, such as planetary mixers or kneaders, may be used.
[0059] In a further embodiment, the metal pigment surface may be additionally modified with a dispersing additive, which is preferably suitable for aqueous systems.
[0060] The dispersant can be used without limitation as long as it can be used in pigment inks, and examples include cationic dispersants, anionic dispersants, nonionic dispersants, and surfactants.
[0061] Examples of anionic dispersants include polyacrylic acid, polymethacrylic acid, acrylic acid acrylonitrile copolymers, vinyl acetate acrylic acid ester copolymers, acrylic acid alkyl acrylate ester copolymers, styrene acrylic acid copolymers, styrene methacrylic acid copolymers, styrene-acrylic acid-alkyl acrylate ester copolymers, styrene-methacrylic acid-alkyl acrylate ester copolymers, styrene-α-methylstyrene-acrylic acid copolymers, styrene-α-methylstyrene-acrylic acid-alkyl acrylate ester copolymers, styrene-maleic acid copolymers, vinyl naphthalene-maleic acid copolymers, vinyl acetate-ethylene copolymers, vinyl acetate-fatty acid vinyl ethylene copolymers, vinyl acetate-maleic acid ester copolymers, vinyl acetate-crotonic acid copolymers, and vinyl acetate-acrylic acid copolymers.
[0062] Examples of nonionic dispersants include polyvinylpyrrolidone, polypropylene glycol, and vinylpyrrolidone-vinyl acetate copolymer.
[0063] Examples of surfactants as dispersants include anionic surfactants such as sodium dodecylbenzenesulfonate, sodium laurate, and ammonium salts of polyoxyethylene alkyl ether sulfates; and nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkyl phenyl ethers, polyoxyethylene alkyl amines, and polyoxyethylene alkyl amides.
[0064] Examples of dispersing additives are Disperbyk 118, Disperbyk 180, Disperbyk 181, Disperbyk 182, Disperbyk 184, Disperbyk 185, Disperbyk 187, Disperbyk 190, Disperbyk 191, Disperbyk 192, Disperbyk 193, Disperbyk 194-N, Disperbyk 199, Disperbyk 2010, Disperbyk 2012, Disperbyk 2013, Disperbyk 2014, Disperbyk 2015, Disperbyk 2018, Disperbyk 2019, Disperbyk 2022, Disperbyk 2023, Disperbyk 2055, Disperbyk 2059, Disperbyk Disperbyk 2060, Disperbyk 2061, Disperbyk 2062, Disperbyk 2080, and Disperbyk 2081, all from Byk-Gardener Additives (Wesel, Germany).
[0065] Donor Surface The donor surface of the printing method in a preferred embodiment is a hydrophobic surface, typically made of an elastomer, which may be selected to have the properties disclosed in this description, and is generally prepared from a silicone-based material.
[0066] Poly(dimethyl-siloxane) polymers are silicone-based and have been found to be suitable. In one embodiment, a fluid curable composition was formulated with a combination of three silicone-based polymers: a vinyl-terminated polydimethylsiloxane 5000 cSt (DMS V35, Gelest™, CAS No. 68083-19-2) in an amount of about 44.8 weight percent (wt%) of the total composition, a vinyl-functional polydimethylsiloxane having both terminal and pendant vinyl groups (Polymer XP RV 5000, Evonik™ Hanse, CAS No. 68083-18-1) in an amount of about 19.2%, and a branched vinyl-functional polydimethylsiloxane (VQM Resin-146, Gelest™, CAS No. 68584-83-8) in an amount of about 25.6 wt%. To this mixture of vinyl functional polydimethylsiloxanes, the following were added: a platinum catalyst, such as platinum divinyltetramethyldisiloxane complex (SIP6831.2, Gelest™, CAS No. 68478-92-2) in an amount of about 0.1% by weight, an inhibitor for better control of the curing conditions, Inhibitor 600 (Evonik™ Hanse), in an amount of about 2.6% by weight, and finally, a reactive crosslinker, such as methylhydrosiloxane-dimethylsiloxane copolymer (HMS 301, Gelest™, CAS No. 68037-59-2) in an amount of about 7.7% by weight, which initiates the addition cure. This addition curable composition was then immediately applied with a smooth smoothing knife to the support on the donor surface (e.g., an epoxy sleeve that can be attached to drum 10). The support is optionally treated (e.g., by corona or with a priming material) to improve adhesion of the donor surface material to the support. The applied fluid is cured in a ventilated oven at 100-120° C. for 2 hours, thus forming the donor surface.
[0067] The hydrophobicity allows the particles to be selectively released by an adhesive film formed on the receiving layer-bearing substrate, thus allowing clean transfer to the substrate without tearing.
[0068] The donor surface should be hydrophobic, i.e. the wetting angle of the particles with the aqueous carrier should be greater than 90°. The wetting angle is the angle formed by the meniscus at the liquid / air / solid interface, and if it is greater than 90°, water will tend to bead up and not wet and therefore adhere to the surface. The wetting angle or equilibrium contact angle Θ0, which is the receding (minimum) contact angle Θ r and the advancing (maximum) contact angle Θ A and can be calculated from these and evaluated at a given temperature and pressure for the operating conditions of the method. It can be conventionally measured with a goniometer or with a drop shape analyzer through a drop with a volume of 5 μl, the liquid-vapor interface contacting the solid polymer surface at ambient temperature (about 23° C.) and pressure (about 100 kPa). The contact angle measurement can be carried out, for example, with a contact angle analyzer-Kruss™; "Easy Drop" FM40Mk2, using distilled water as the reference liquid.
[0069] This hydrophobicity may be an inherent property of the polymer forming the donor surface, or it may be enhanced by adding hydrophobic additives into the polymer composition. Additives that may promote the hydrophobicity of the polymer composition may be, for example, oils (e.g., synthetic, natural, vegetable or mineral oils), waxes, plasticizers and silicone additives. Such hydrophobic additives may be compatible with the polymer material, as long as their respective chemical nature or amount will not interfere with the formation of the donor surface and will not, for example, interfere with the proper curing of the polymer material.
[0070] The roughness or finish of the donor surface is reproduced in the printed metallized surface. Thus, if a mirror finish or highly glossy appearance is required, the donor surface may need to be smoother than if a matte or satin appearance is desired. These visual effects may also result from roughness in the print substrate and / or receiver layer.
[0071] Although the donor surface in the drawing is the outer surface of a drum, this is not essential, since it may alternatively be the surface of an endless transport member, which has the form of a belt extending over guide rollers and which is under suitable tension at least while it passes through the coating device. Additional configurations may allow the donor surface and the coating station to move relative to each other. For example, the donor surface may form a mobile configuration, which may repeatedly pass under a static coating station, or may form a static configuration, which repeatedly moves from one end of the configuration to the other, so that the donor surface is entirely covered with particles. It is envisaged that both the donor surface and the coating station may move relative to each other and relative to a stationary point in space, so that the time that may be required for the entire coating of the donor surface with the particles provided by the coating station to be achieved is reduced. All such configurations of the donor surface may be movable (e.g., in a rotational manner, annular manner, endless manner, repeating manner, movable, etc.) relative to the coating station, where the donor surface so passing can be coated with particles (or replenished with particles in exposed areas).
[0072] The donor surface may additionally accommodate practical or specific considerations arising from the particular configuration of the printing system: for example, it may be sufficiently flexible to be mounted onto a drum, may be sufficiently scratch resistant, may be inert to the particles and / or fluids used, and / or may be resistant to any operating conditions of interest (e.g., pressure, heat, tension, etc.). Satisfying such characteristics tends to favorably increase the life of the donor surface.
[0073] The donor surface, whether formed as a sleeve over a drum or as a belt over a guide roller, may further have a body on the opposite side of the particle-receiving outer layer, which together with the donor surface may be referred to as a transfer member. This body may have different layers, each of which imparts one or more desired properties to the overall transfer member, such as mechanical resistance, thermal conductivity, compressibility (e.g., compressibility to improve the "macroscopic" contact between the donor surface and the print cylinder), compatibility (e.g., compatibility to improve the "microscopic" contact between the donor surface and the print substrate on the print cylinder), and any other property that is readily understood by those skilled in the art of print transfer members.
[0074] A further aspect of the invention is directed to the use of particles in a method for printing on a surface of a substrate, at least 50% by weight of the particles being flaky metal pigments, the flaky metal pigments comprising a flaky metal substrate and a surface modification layer of the metal substrate, the surface modification layer being formed by treatment of the metal substrate surface with at least one modifying agent, the at least one modifying agent being at least one modifying agent from the group consisting of phosphate esters, phosphonate esters, phosphonic acids, phosphinate esters, organofunctional silanes, organofunctional titanates, organofunctional zirconates, organofunctional aluminates, and mixtures thereof; This method is (a) providing a donor surface; (b) passing the donor surface through a coating station, the donor surface emerging from the coating station coated with a monolayer of individual particles; and (c) repeatedly performing the steps of: (i) treating a surface of the substrate such that the affinity of the particles for at least selected regions of the surface of the substrate is greater than the affinity of the particles for the donor surface; (ii) contacting a surface of the substrate with a donor surface to transfer particles from the donor surface to only the treated selected areas of the surface of the substrate, thereby exposing areas of the donor surface to which the particles will be transferred to corresponding areas on the substrate; (iii) thus producing a plurality of individual particles adhered to the treated surface of the substrate; Returning the donor surface to the coating station to make the particle monolayer continuous, thereby allowing printing of a subsequent image on the surface of the substrate.
[0075] All features, aspects and preferred aspects of the printing method disclosed in the present invention apply equally to the use of particles in the printing method described above. EXAMPLES
[0076] Example 1a: A specific amount of aluminum flake paste (VP-68680 / G IL, Eckart) was homogenized in a kneader. VP-68680 / G IL was produced by milling method and had a median thickness of about 24 nm and a diameter of about 2.5 μm. 50 The additive Hostaphat CC100 was dissolved in isopropanol. From this solution, a measured amount was added to the aluminum paste in the kneader, so that a total of 2.0% by weight of additive was added relative to the aluminum flakes. The mixture was homogenized for a further 5 minutes and the amount of solids was fixed at 65% by weight by adding isopropanol.
[0077] Example 1b: As in Example 1, but with 2.0 wt. % Hostaphat CC100 plus additionally 2.0 wt. % Disperbyk 192 as dispersing additive (each relative to the Al flake content).
[0078] Example 1c: As in Example 1, but with the addition of 3.0 wt. % Hostaphat CC100 dispersion additive (relative to the Al flake content).
[0079] Comparative Example 1: VP-68680 / G IL without additive treatment
[0080] Example 2a: Al: Metalure A-31510EN + 3% Hostaphat CC100 Lab Mixer (PVD-pigment) As in Example 1a, however, a lab mixer was used as agglomerator and a commercial dispersion of PVD aluminum effect pigment in ethyl acetate (Metalure® A-41010AE, 10% aluminum content by weight) was mixed as an aluminum flake paste. 50 = 10 μm, Eckart America) and as additive 3.0% by weight of cetyl phosphate ester (Hostaphat CC100) based on the metal content of the aluminum effect pigment was used. The final content of solids of the dispersion in ethyl acetate was 10% by weight.
[0081] Example 2b: As in Example 2a, however, together with the additive an additional 3.0 wt. % of the dispersing additive Disperbyk™ 192 was added.
[0082] Example 2c: As in Example 2a, but using 3.0 wt. % lauryl phosphate monoester as the additive (Fisher Scientific 11332727).
[0083] Example 2d: As in Example 2c, however, together with the additive an additional 3.0 wt. % of the dispersing additive Disperbyk 192 was added.
[0084] Comparative Example 2: Metalure A-41010AE (10% aluminum content) without additive treatment
[0085] Example 3a: As in Example 1a, but using a lab mixer as the mixer agglomerator, a filter cake of VP-66762 / G IL (Eckart) as the aluminum flake paste, and 2.0 wt. % OPS as the additive. The final solid content of the paste was 25 wt. %. VP-66762 / G IL is a very thin aluminum effect pigment produced by milling, with a median thickness of about 35 nm and a d of about 9 μm. 50 has.
[0086] Example 3b: As in Example 3a, however, along with the additive, an additional 2.0 wt% Disperbyk 192 was added (2.0 wt% OPS).
[0087] Example 3c: (D32): Al: VP-66762 / G IL FK + 2% Hostaphat CC 100, Lab mixer, same as in Example 3a, but with 2.0 wt% Hostaphat CC100 as additive.
[0088] Comparative Example 3: VP-66762 / G IL without additive treatment
[0089] Comparative Example 4: 35.49 pbw non-leaf aluminum pigment, produced by vacuum metallization, dispersed in isopropanol, solid content 20 wt%, average particle thickness 30-45 nm, particle size distribution (d10 / d50 / d90): 4μm / 7.9μm / 15.5μm, 43.09 pbw of isopropanol was mixed well until a dispersion was obtained. 0.02 pbw of peroxomolybdic acid solution (1 pbw of molybdic acid mixed with 3 pbw of 30% aqueous hydrogen peroxide) was added and mixing was continued. The dispersion was then heated to 80°C and 3.71 pbw of tetraethoxysilane (TEOS), 5.20 pbw of water, and 0.56 pbw of acetic acid were added. The mixture was stirred for a period of time while maintaining the temperature at 80°C.
[0090] Intermittently, 0.28 pbw of ethylenediamine and 3.55 pbw of isopropanol were added with continued stirring at 80° C. until a total of 0.84 pbw of ethylenediamine had been added. Stirring at 80° C. was continued for several hours, after which the mixture was cooled and some of the solvent was removed to yield a paste of entrapped aluminum particles.
[0091] The aluminum particle pastes obtained in each of Examples 1 to 3 were dispersed in water and applied to a substrate using the method described in WO2016 / 189515A9.
[0092] As comparative examples, pastes of aluminum flakes of the respective metal pigments without additive treatment were used, which were dispersed in water and applied to a substrate using the printing method described in WO2016 / 189515A9.
[0093] [Table 1]
[0094] The transfer of the metallic pigment to the donor surface and the printability onto the substrate were also evaluated. The gloss, optical density, gloss retention and corrosion resistance of the samples thus prepared were measured. The results are shown in Table 1.
[0095] By gloss retention, we mean measuring the gloss after repeated printing operations over a period of time. For example, after printing, the gloss was measured after 1 day, after 2 days, and finally up to 30 days. If the gloss after 30 days was not less than 95% of the initial gloss, the gloss retention was rated "very good." If the gloss after 30 days was not less than 90% of the initial gloss, the gloss retention was rated "very good."
[0096] Gloss retention was rated as "defective" if the gloss was less than 50% of the initial gloss.
[0097] Gross Measurement: The gloss of the metallized surface of the print samples was measured using a gloss meter (instrument: MicroTRI Gloss (BYK-Gardner, D-82538, Geretstied, Germany)). As the measured surfaces are highly reflective, the measurements were performed using a 20° angle setting. For each sample, five measurements in different areas were performed and these values were arithmetically averaged.
[0098] Optical Density (OD) Measurement The optical density provides an indication of the amount of metallic pigment transferred. To determine the optical density, a black / white transmission hydrometer (instrument: 341C, X-Rite, Grand Rapids MI 49512, USA) was used. To calibrate, a virgin substrate was first measured and the value was set to zero. For each sample, three measurements in different areas were performed and these values were arithmetically averaged. An OD below 0.40 was not a satisfactory transfer of metallic pigment.
[0099] The samples prepared with aluminum particles of Examples 1-3 all showed high initial gloss levels, good gloss retention, and good corrosion stability. In particular, the coated metal effect pigment according to Example 2 (PVD pigment) showed a high average gloss of about 600 gloss units measured at 20°. The substrates printed with Comparative Examples 1 and 2 showed high to reasonable initial gloss levels, but poor gloss retention, since the samples showed corrosion in aqueous media within about 2 days after application. Furthermore, the OD values were generally lower compared to the respective Examples, indicating relatively poor transfer to the substrate.
[0100] In contrast to the other examples and Comparative Examples 1 and 3, the effect pigments of Comparative Examples 2 and 4 were not transferred to the donor surface in sufficient amounts, and therefore the printing results on the substrate were not satisfactory.
Claims
1. 1. A method of printing on a surface of a substrate, the method comprising: a. providing a donor surface; b. passing the donor surface through a coating station, the donor surface emerging from the coating station coated with individual particles; and c. Repeatedly carrying out the following steps: i. treating the surface of the substrate to cause the affinity of the particles for at least selected regions of the surface of the substrate to be greater than the affinity of the particles for the donor surface, wherein a receptor layer and / or an adhesive layer is applied to the substrate; ii. contacting the surface of the substrate with the donor surface such that particles are transferred from the donor surface to only the treated selected areas of the surface of the substrate, thereby exposing areas of the donor surface for particle transfer to corresponding areas on the substrate; iii. Thus producing a plurality of individual particles adhered to the treated surface of the substrate; iv. returning the donor surface to the coating station to make the particle monolayer continuous, thereby allowing subsequent printing of images onto the surface of the substrate; Including, The method comprises: At least 50% by weight of the individual particles are flake metal pigments comprising a flake metal substrate and a surface modification layer of the metal substrate, the surface modification being formed by treating the metal substrate surface with at least one modifying substance selected from the group consisting of phosphate esters, phosphonate esters, phosphonic acids, phosphinate esters, organofunctional silanes, organofunctional titanates, organofunctional zirconates, organofunctional aluminates, and mixtures thereof. method.
2. The method of claim 1 , wherein in step b, the donor surface leaves the coating station coated with a monolayer of individual particles.
3. The flaky metal substrate has an average thickness (h) in the range of 10 to 500 nm, preferably 15 to 40 nm. 50 The method according to claim 1 or 2, wherein the first and second values are
4. The flaky metal substrate has an aspect ratio in the range of 1500:1 to 10:1, the aspect ratio being smaller than the average pigment diameter (D 50 value) and the average (median) pigment thickness (h 50 The method according to any one of claims 1 to 3, wherein the ratio between the α and β values is defined as:
5. 5. The method according to any one of claims 1 to 4, wherein the flaky metal substrate is selected from flaky substrates of aluminium, copper, zinc, gold-bronze, chromium, titanium, zirconium, tin, iron and steel or pigments of alloys of these metals.
6. The method according to any one of claims 1 to 5, wherein the flaky metal substrate is formed by a PVD method, preferably an aluminum pigment.
7. The method according to any one of claims 1 to 6, wherein the flaky metal substrate further contains up to 30% by weight of an oxide, hydroxide, acid hydrate, or mixture thereof, of the same metal on its surface, and the modifier is bonded to the metal oxide.
8. The method according to any one of claims 1 to 7, wherein the modifier is at least one of the following: (i)[R-O] (n-o-p) P(O)(OR 1 ) o (OR 2 ) p where o=1 to 2, p=0 to 2, and n+o+p=3 or 2; (ii) R (n-o-p) -P(O)(OR 1 ) o (OR 2 ) p And n+o+p=3 (iii)R-P(OR 1 )(OR 2 ) (iv)R´-SiX 3 X is a halogen group, OH, or alkoxy (OR 3 ) and R 3 = methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl; R 1 and R 2 is H, a metal ion, or a linear or branched alkyl moiety of 1-4 C atoms, and R or R′ is a linear or branched alkyl, aryl, alkylaryl, or arylalkyl moiety having 1-24 C atoms, which may be further functionalized by a functional group; (v)R´´zSiX (4-z) (vi)R´R´´SiX 2 In formula (v), z is an integer from 1 to 3; in formula (v) or (vi), R″ is an unsubstituted, unbranched or branched alkyl chain having 1 to 24 C atoms, or an aryl group having 6 to 18 C atoms, or an arylalkyl or alkylaryl group having 7 to 25 C atoms, or a combination thereof; and X is a halogen group and / or preferably an alkoxy group; Or, (vii) Precondensed polyheterosiloxanes.
9. 9. The method of claim 8, wherein the functional groups of the moieties R or R' are independently selected from the group consisting of phosphonic, phosphate, amino, epoxy, acrylate, methacrylate, hydroxy, mercapto, thiol, cyano, isocyanate, carboxy, carbamate, ureido, and thioureido groups.
10. The method according to claim 8 or 9, wherein the additive is an α,ω-diphosphonic acid or an α,ω-diphosphate ester.
11. The method according to any one of claims 1 to 10, wherein the metal pigment surface may additionally be modified by a dispersing additive.
12. The method according to any one of claims 1 to 11, wherein the donor surface is a hydrophobic surface, preferably formed by an elastomer prepared from a poly(dimethylsiloxane) polymer.
13. Use of a plurality of particles in a method of printing on a surface of a substrate, comprising the steps of: at least 50% by weight of the plurality of particles is a flake metal pigment comprising a flake metal substrate and a surface modification layer of the metal substrate, the surface modification layer being formed by treating the metal substrate surface with at least one modifying agent selected from the group consisting of phosphonate esters, phosphinate esters, phosphonic acids, organofunctional silanes, organofunctional titanates, organofunctional zirconates, organofunctional aluminates, and mixtures thereof; The method further comprising: a. providing a donor surface; b. passing the donor surface through a coating station, the donor surface emerging from the coating station coated with a monolayer of individual particles; and c. Repeatedly carrying out the following steps: i. treating the surface of the substrate to cause the affinity of the particles for at least selected regions of the surface of the substrate to be greater than the affinity of the particles for the donor surface, wherein a receptor layer and / or an adhesive layer is applied to the substrate; ii. contacting the surface of the substrate with the donor surface such that particles are transferred from the donor surface to only the treated selected areas of the surface of the substrate, thereby exposing areas of the donor surface for particle transfer to corresponding areas on the substrate; iii. Thus producing a plurality of individual particles adhered to the treated surface of the substrate; iv. returning the donor surface to the coating station to make the monolayer of particles continuous, thereby allowing subsequent printing of images onto the surface of the substrate; Including, use.
14. Use of a plurality of particles according to claim 13 in a printing method according to any one of claims 2 to 12.
Citation Information
Patent Citations
Apparatus and method for three-dimensional shaping
JP2002347129A
Thin coated aluminum pigment, method for its production and use of the aluminum pigment
JP2006522192A
Printing System and Method
JP2018517596A
Surface-modified effect pigments and nail enamel compositions
JP2019516672A
Nail polish compositions containing embossed effect pigments and surface-modified embossed effect pigments
JP2021500343A